STRATEGI PEMASARAN ABON IKAN TUNA (Thunnus sp) PRODUKSI UMKM DI KOTA PAREPARE - Bahari, Aditya Saputra; -, Nurhapsa; -, Arman (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
The purpose of this study is to determine the obstacles of UMKM in the production and marketing activities abon tuna fish and to determine the right marketing strategy to be implemented by UMKM abon tuna in Parepare City. Research on Marketing strategy to increase sales of Abon Tuna Fish in Parepare City was held in July 2017 located in the City of Parepare. Type of research is descriptive research. Sampling using sampling method saturated or census, where all study population used as a sample with the number of 12 UMKM abon tuna data used in this study are primary data and secondary data. The method used in this research is SWOT analysis method. The data obtained are qualitative and quantitative data of respondents interview which then analyzed by using SWOT analysis method. The results showed that alternative marketing strategy appropriate to increase sales of Abon Tuna Fish at UMKM Abon Tuna Fish in Parepare City is a strategy of SO (strategy to utilize the strength of UMKM so as to seize the opportunity). The strategy that should be applied under these conditions is an aggressive strategy. In this case the power of UMKM can be utilized to obtain great opportunities.